2018
DOI: 10.3329/pa.v29i2.38300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spirulina platensis on alloxan induced diabetic rats

Abstract: The study was undertaken to investigate the effects of Spirulina platensis on body weight, blood glucose and lipid profile on alloxan induced diabetic rats. Fifteen Long Evans male rats at six weeks of age were used for the experiment. Diabetes was induced by intraperitoneal injection of alloxan@ 150 mg/kg and experiment was carried out for a period of 6 weeks. Rats were divided into three groups of 5 rats each. The groups were i)healthy control, ii) diabetic control with both receiving rats’ pellet as supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…(28) Effect on lipid profile Diabetic rats exhibited a significant increase in serum TC, triglyceride and LDL-C when compared to normal control rats. This comes in agreement with Hussaini et al, (2018) (29) who reported that Alloxan causes hyperlipidemia in animals. In the current study, there was a significant reduction in serum TC, triglyceride and LDL-C and improvement in HDL-C of diabetic rats treated with different tested doses of Spirulina platensis as compared with diabetic control.…”
Section: Effect On Fbg Levelsupporting
confidence: 93%
“…(28) Effect on lipid profile Diabetic rats exhibited a significant increase in serum TC, triglyceride and LDL-C when compared to normal control rats. This comes in agreement with Hussaini et al, (2018) (29) who reported that Alloxan causes hyperlipidemia in animals. In the current study, there was a significant reduction in serum TC, triglyceride and LDL-C and improvement in HDL-C of diabetic rats treated with different tested doses of Spirulina platensis as compared with diabetic control.…”
Section: Effect On Fbg Levelsupporting
confidence: 93%
“…In this connection, diabetic rats treated with Spirulina maxima showed a regain in their body weight which may be explained by the increased insulin secretion or the increased food consumption (Pandey et al, 2010). Likewise, oral administration of S. platensis aqueous extract to diabetic rats for 50 days led to an obvious regain in their body weight loss, suggesting general health status and metabolic mechanisms improvement by effective control of glycemia or reversing of gluconeogenesis (Aissaoui et al, 2017;Hussaini et al, 2018).…”
Section: Effect Of S Platensis Methanolic Extract On the Body Weightmentioning
confidence: 99%
“…The hypoglycemic effect of Spirulina maxima or S. platensis powder aids in the diabetes treatment by controlling the increased blood glucose levels in the streptozotocin (STZ) induced diabetic animals (Pandey et al, 2011;Ripa et al, 2018). Moreover, the administration of 400 mg/Kg of S. platensis powder could reduce the adverse effect of plasma hyperglycemia in the alloxan induced diabetic rats as recommended by Hussaini et al (2018) and Okechukwu et al (2019). The possible mechanism by which Spirulina brings about its antihyperglycemic action may be through improving the pancreatic secretion of insulin from β-cell islets or due to enhanced transportation of blood glucose to the peripheral tissue in the Spirulina -treated diabetic rats (El-Baz et al, 2013).…”
Section: Gas Chromatography-mass Spectrum (Gc-ms) Analysis Of S Platensis Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, diabetic rabbits, when fed with Arthrospira platensis (Cyanobacteria) powder, showed antihyperglycemic activity by lowering their blood glucose levels [106]. Moreover, the administration of 400 mg/Kg of A. platensis powder could reduce the adverse effect of hyperglycemia in the alloxan-induced diabetic rats [107]. Besides, the antioxidants compounds detected in A. platensis extract can aid to prevent diabetes or alleviate its adverse effects on blood parameters and the inflammatory phase [108].…”
Section: In Vivo Antihyperglycemic Activity Of Algaementioning
confidence: 99%